A Study to Assess the Effect of Food Consumption Pattern on Health Status among Nursing Students at Dinsha Patel College of Nursing, Nadiad - Dhara Vyas; Fiza Sherasiya; Ami Patel (Indian Journal of Forensic Medicine & Toxicology, 2021)
College students are at risk for making poor dietary choices that can cause significant health problems. Adescriptive study was conducted to assess the effect of food consumption pattern on health status amongnursing students at Dinsha Patel College of Nursing, Nadiad. A sample of 101students was selected bysystematic random sampling technique. Five point Likert Scale was used to assess the food consumptionpattern. The data was analyzed by using the descriptive and inferential statistics. The result of present studyreveals 50(49%) students have more than 11 g/dl hemoglobin level, 56(55%) students are underweight,73(72 %) students believes that they are taking balance diet. There is a statistically significant associationwith the perception regarding balanced diet and food consumption pattern and no significant associationwith other socio demographic variables such as age, sex, education, BMI, Hemoglobin level, religion,eating habits, residential status. The result shows 37(36.6%) students had unhealthy, 44(43.5%) studentshad average healthy, 19(18.8%) students had healthy diet pattern The study concluded that there is a need forhealth education programs that promote healthy food consumption pattern for nursing students.